Molecular Identification of Pathogenic Klebsiella Pneumoniae Strains Producing Biofilm (Medico Legal Update, 2020)
Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infections with production ofbiofilm. In the current study, 73 samples were collected from both patient genders of different ages sufferingof burn and wound injuries that referred to four hospitals in Baghdad city from Aug. to Nov. 2019. Thesamples were cultured on MacConkey agar and 60 bacterial isolates were obtained. Primary identificationby cultural and microscopic examinations declared that all isolates belong to genus Klebsiella. Then the 60isolates were identified by Vitek 2 system which insured they were belonged to Klebsiella pneumoniae. Theidentified isolates were screened for ability to produce biofilm by Microtiter Plate technique and Congo redagar method. Results showed that only 4 isolates (3 of wounds and 1of burns) were able to form biofilms.Upon such important characteristic, the four isolates were submitted to the 16S rRNA gene amplification testby using PCR technique and results declared that they are certainly belong to Klebsiella pneumoniae. The“National Center for Biotechnology Information (NCBI)” verified and documented that they are new strainsof Klebsiella pneumoniae to be discovered in this study for the first time and registered them as; KPWIQ25,KPWIQ49, KPWIQ51 and KPBIQ19 strains of Klebsiella pneumoniae.